Delirium in older patients: a diagnostic study of NEECHAM Confusion Scale in surgical intensive care unit. Issue 19 (2nd November 2012) - Matarese, Maria; Generoso, Stefano; Ivziku, Dhurata; Pedone, Claudio; De Marinis, Maria Grazia
Abstract : Aims and objectives: To estimate the diagnostic value and determine the feasibility of the NEECHAM Confusion Scale on critically ill older patients. Background: Delirium is a common syndrome in hospitalised older patients, especially in surgical intensive care units, and the consequences of under‐detection can be very serious for older people. Therefore, assessment of the cognitive status of older patients using a valid instrument is important in intensive care units. Design: A descriptive prospective design was used. Methods: Consecutive nonintubated patients aged 65 and older, admitted to a surgical intensive care unit of an Italian hospital during a seven months period, were assessed for delirium using the NEECHAM scale and the Confusion Assessment Method for intensive care unit, once per shift, for 48 hours after admission. Cohen's kappa coefficient, ROC curve, sensitivity and specificity were estimated. An open ended questionnaire was used to assess user‐friendliness of the scale. Results: A sample of 41 older patients with a mean age of 78·3 years was studied. The kappa coefficient was 0·95. The sensitivity was 99·19%, specificity 95% at cut‐off of 25, and the area under the curve was 0·99 (CI 0·99–1·00). Nurses evaluated positively the scale as they were able to collect data during care process in maximum 10 minutes, but experienced problems in rating the appearance behaviour and physiological control items of the scale. Conclusions: Findings from this study confirm the good diagnostic value and ease of application of the NEECHAM scale with nonventilated intensive care patients. Relevance to clinical practice: The NEECHAM scale can be used to detect delirium during the routine nursing assessment of nonintubated older patients as it requires minimal demand and stress on the patient as well as on the bedside nurse.